New reproductive locations for the common spadefoot toad Pelobates fuscus (Anura: Pelobatidae) in Como province, Italy - Larroux, Nicola; Seglie, Daniele; Ferrario, Alberto; Eusebio Bergò, Paolo; Cavalcante, Riccardo; Mologni, Andrea; Soldato, Giovanni (Natural History Sciences, 2025)
The common spadefoot toad Pelobates fuscus is a highly protected amphibian species, vulnerable to habitat fragmentation and numerous other environmental changes. This note reports the discovery of new reproductive sites for the species in Como province, representing the northernmost locations known in Italy to date. These findings underscore the ecological importance of small, neglected wetlands in sustaining amphibian populations. Field surveys conducted from July 2024 to March 2025 assured the reproduction of P. fuscus alongside other protected amphibian species. These discoveries also suggest probable undocumented populations in the nearby areas comprising the Swiss region, where P. fuscus was last recorded in 1946. Given the species’ cryptic nature and fragmented distribution, further research integrating traditional surveys and molecular techniques is essential to reassess its actual range and develop effective conservation strategies.